2020
DOI: 10.1093/sleep/zsaa070
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to management of sleep-associated problems in patients with breast cancer (MOSAIC) during chemotherapy : A pilot study

Abstract: Study Objectives This pilot randomized controlled trial (RCT) was conducted to assess the preliminary effects of Brief Behavioral Therapy for Cancer-Related Insomnia (BBT-CI) delivered by trained research staff in comparison to a sleep hygiene pamphlet control and to assess moderators of treatment effect in patients with breast cancer undergoing chemotherapy. Methods Of 74 participants recruited, 37 were randomized to BBT-CI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…17,18 Remotely delivered CBT-I interventions have largely relied on technologies that are asynchronous (eg, video recordings 35 ), lack a facilitator (eg, an app or website 16,[19][20][21][22]36 ), or have hybrid in-person and remote sessions (eg, brief behavioral therapy for insomnia 37 ). As noted previously, 35,38 survivors expressed that professional support is necessary to stay engaged in CBT-I sessions and to personalize treatment based on cancer-related experiences. These preferences were substantiated by our RCT findings, which demonstrated rates of session attendance (100%) and retention across assessments (90% at 1month follow-up) that were higher than in other CBT-I trials among cancer survivors.…”
Section: Discussionmentioning
confidence: 89%
“…17,18 Remotely delivered CBT-I interventions have largely relied on technologies that are asynchronous (eg, video recordings 35 ), lack a facilitator (eg, an app or website 16,[19][20][21][22]36 ), or have hybrid in-person and remote sessions (eg, brief behavioral therapy for insomnia 37 ). As noted previously, 35,38 survivors expressed that professional support is necessary to stay engaged in CBT-I sessions and to personalize treatment based on cancer-related experiences. These preferences were substantiated by our RCT findings, which demonstrated rates of session attendance (100%) and retention across assessments (90% at 1month follow-up) that were higher than in other CBT-I trials among cancer survivors.…”
Section: Discussionmentioning
confidence: 89%
“…Among cancer survivors who had completed active treatment (including surgery, chemotherapy, and radiotherapy), Garland et al 12 found that 8-week of treatment produced 8.3 points reduction in ISI in acupuncture group and 10.9 points in cognitive behavioral therapy group respectively compared to pre-treatment.In our study, 6-week of acupuncture treatment produced 6.6 points reduction in ISI compared to pre-treatment among breast cancer patients undergoing active treatments. In another study, Palesh et al 37 investigated the effectiveness of brief behavioral therapy for insomnia among breast cancer patients receiving chemotherapy, and found that 6-week of treatment produced around 5 points reduction in ISI as compared with pre-treatment. Cancer survivors who had completed active cancer treatment seemed to benefit more from acupuncture or behavioral therapy as compared to those who were undergoing active treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The study interventions are described elsewhere in detail 24,33,34 . Briefly, BBT‐CI consisted of 6 sessions: 2 face‐to‐face sessions and four 15‐minute phone calls, including the following components: 1) chronorehabilitation education and techniques (eg, the connection between sleep, circadian disruption, and cancer), 2) light and stimulus control (increase light exposure during the day, minimize light exposure at night; education about melatonin as a circadian hormone; and associate the bed with sleep and sex only), 3) encouragement of sleep activity and protocol for napping, and 4) sleep compression (go to bed later by 15 minutes if sleep quality is low).…”
Section: Methodsmentioning
confidence: 99%